The hive queen - Sutherland, Tui, 1978- (New York : Scholastic Inc., 2019)
Growing up in the hives, Cricket has always had a million questions some of which put her in danger. Whenever the queen takes control of all the HiveWings, speaking through their mouths and seeing through their eyes, Cricket has to hide, terrified of being discovered. Now she's hiding again, wanted for stealing the Book of Clearsight along with her new SilkWing friends, Blue and Swordtail, and the fierce LeafWing, Sundew. The fugitives need answers, and fast, in order to prevent a LeafWing attack. But Cricket has more questions than ever. How can she stay hidden and discover the queen's deadliest secret? And if she does succeed--can a powerless dragonet really do anything to topple a regime and stop a war?
5.5
3-6
770L
Keywords: Dragons -- Juvenile fiction; Friendship -- Juvenile fiction; Dragons -- Fiction; Friendship -- Fiction; Fantasy fiction; Action and adventure fiction